KONSEP KONSELOR PERSPEKTIF QUR’AN ;TAFSIR AL-QUR’AN AN-NAHL AYAT 125-128 - Irma, Irma Suryani Nasution; Hasan Zaini; Irman (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Today's problems are not problems that can be overcome easily, they need appropriate methods or methods as well as characteristics that encourage the counseling process carried out by the counselor to run smoothly. This research aims to find out the concept of a counselor from a Qur'anic perspective in Surah An-Nahl verses 125-128. This research method uses a qualitative method with a library research approach. Data sources obtained from commentary books, articles and other printed materials. The results of this research show that the concept of a counselor can apply the methods and characteristics that a counselor must possess in accordance with Surah An-Nahl verses 125-128. Being a counselor in carrying out his duties resolves client problems in accordance with the teachings of the Al-Qur'an and hadith and has full awareness of being a useful human being for the counselee